PERBANDINGAN SHOOTING KETIGA BAGIAN KAKI TERHADAP KETEPATAN SHOOTING PEMAIN SEPAKBOLA PADA UKM SEPAKBOLA UNIVERSITAS GARUT - N, Muhammad Asyhari; Permadi, Asep Angga; Sonjaya, Azhar Ramadhana (Fakultas Ilmu Keolahragaan Unimed, 2024)
Comparison between the shooting of the three parts of the foot on the shooting accuracy of UNIGA football UKM football players. The method used in this research is descriptive comparative with a quantitative approach. Based on the normality test results, it is knownthat the overall data is 0.200 and 0.177 > 0.05 and is normally distributed, and the homogeneity test results show that the sig. 0.197; 0.613; 0.705 > 0.05 so it can be stated that all data is homogeneous. Then the researcher tested the hypothesis using correlation with sig results. > 0.05 so that H1 is accepted and H¬0 is rejected and it can be seen that there is a comparison between the three parts of the foot (inner leg, outer leg and back leg) with shooting accuracy in the football game of UNIGA football UKM students. Based on the research results, it can be seen that shooting accuracy can be influenced by the three parts of the foot, because there is a comparison between the three parts of the foot (inner leg, outer leg and back leg) and shooting accuracy in football games for UNIGA football UKM students. From the statement above we can conclude that shooting accuracy is influenced by the three parts of the foot. Knowing that the shooting skills of UNIGA football UKM students have a comparison between the three parts of the foot and shooting accuracy, it is necessary to pay attention to improving shooting skills with a program to improve shooting skills on the three parts of the foot.again the forward. Abstract in Indonesian can be a translation of an English translation. Tiff editor for abstract syncing for reasons of abstract content